REPORT ON THE CORINDON CRUISES - Moosa, Mohammad Kasim (Marine Research in Indonesia, 1984)
The corindon cruises were the first realization of the Cooperation on Oceanology between the governments of France and Indonesia. The name Corindon is derived from the name of French vessel "CORIOLIS" and Indonesia to signify that the vessel was participating in marine research activities in Indonesian waters.